Sporotrichosis in cats: ABCD guidelines on prevention and management. Issue 7 (July 2013) - Lloret, Albert; Hartmann, Katrin; Pennisi, Maria Grazia; Ferrer, Lluis; Addie, Diane; Belák, Sándor; Boucraut-Baralon, Corine; Egberink, Herman; Frymus, Tadeusz; Gruffydd-Jones, Tim; Hosie, Margaret J; Lutz, Hans; et al.
Overview: Sporotrichosis is an important subcutaneous fungal infection of humans and animals in some endemic tropical and subtropical areas. Among domestic species, cats are the most frequently infected. Infection: The primary mode of transmission is traumatic inoculation of fungal conidia from plants and soil. Contact with infected cats is the major mode of transmission to humans, especially in endemic areas like Brazil, where a large epidemic has occurred in the past decade. Disease signs: Most cases in cats are cutaneous, presenting as multiple ulcerated nodules and draining tracts in the skin. Lymphadenopathy, respiratory signs and systemic dissemination may also occur. Diagnosis: Diagnosis is based on fungal detection by cytology and/or histology, and confirmation by culture. Treatment: Treatment consists of at least 2 months' systemic antifungal therapy, with itraconazole as the first-choice agent. The prognosis is favourable provided there is good owner compliance and adverse drug effects do not occur. Prevention: Contact with infected cats carries a high zoonotic risk. Cat owners travelling to endemic areas should be warned and advised to keep their cats indoors to prevent infection. Professionals must wear gloves when handling cats with skin nodules and ulcers and dealing with diagnostic samples.